Novelties in acute rheumatic fever [Akut romatizmal ateş ve yenilikler] - (:unkn) unknown (Kare Publishing, 2007)
While the incidence and importance of acute rheumatic fever has been declining in industrialized countries, it remains as the most important cause of acquired heart disease in developing or undeveloped countries. About 3 to 6 % of any population is considered to be susceptible to rheumatic fever. Although it is common between the ages of 5 and 15, the patients under five years comprise 3-5 % of the total number. Acute rheumatic fever is diagnosed using the Jones criteria updated by the World Health Organization in 2003. During the first attack two major or one major+two minor manifestations in the presence of evidence of recent streptococcal throat infection is a high probability of rheumatic fever. Major manifestations are migratory polyarthritis, carditis, chorea, erythema marginatum and subcutaneous nodules; minor manifestations are fever over 38°C, arthralgia, elevated acute phase reactants (ESR>60mm/hr, C-reactive protein (+)) and prolongation of PR interval on electrocardiogram. Positive throat culture for streptococci, elevated/increasing ASO titers and history of scarlet fever are accepted as evidences of recent streptococcal infection. The role of echocardiography has increased in recent years. When echocardiography is not performed subclinical valvular involvements are not recognized and these patients may present with rheumatic heart disease in the future. Bed-chair rest, antibiotic treatment, anti-inflammatory treatment, the treatment for congestive heart failure and sedation in patients with chorea are options for management of rheumatic fever. The only intervention proven to affect long term prognosis is secondary prophylaxis. In conclusion rheumatic fever may present in various appearances and still bites the heart.
Keywords: Acute rheumatic fever; Jones criteria; Rheumatic heart disease